The role and mechanisms of macrophage polarization and hepatocyte pyroptosis in acute liver failure - Xie, Dan; Ouyang, Shi (Frontiers in Immunology, 2023)
Acute liver failure (ALF) is a severe liver disease caused by disruptions in the body's immune microenvironment. In the early stages of ALF, Kupffer cells (KCs) become depleted and recruit monocytes derived from the bone marrow or abdomen to replace the depleted macrophages entering the liver. These monocytes differentiate into mature macrophages, which are activated in the immune microenvironment of the liver and polarized to perform various functions. Macrophage polarization can occur in two directions: pro-inflammatory M1 macrophages and anti-inflammatory M2 macrophages. Controlling the ratio and direction of M1 and M2 in ALF can help reduce liver injury. However, the liver damage caused by pyroptosis should not be underestimated, as it is a caspase-dependent form of cell death. Inhibiting pyroptosis has been shown to effectively reduce liver damage induced by ALF. Furthermore, macrophage polarization and pyroptosis share common binding sites, signaling pathways, and outcomes. In the review, we describe the role of macrophage polarization and pyroptosis in the pathogenesis of ALF. Additionally, we preliminarily explore the relationship between macrophage polarization and pyroptosis, as well as their effects on ALF.